2013
DOI: 10.1111/den.12214
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and post‐training session evaluation for interobserver agreement and diagnostic accuracy of probe‐based confocal laser endomicroscopy for biliary strictures

Abstract: Interobserver agreement and diagnostic accuracy improved after observers underwent training by an expert pCLE user with a specific sequence set. Users should participate in such training programs to maximize diagnostic accuracy of pCLE evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The inter‐observer agreement in interpretation of probe‐based confocal laser endomicroscopy imaging for indeterminate biliary strictures was reported poor or fair in a prospective, multicentre pilot study . Another prospective, multicentre study showed that the diagnostic accuracy for indeterminate biliary strictures could be improved significantly after training with expert user of probe‐based confocal laser endomicroscopy, which highlights the necessity and importance of training before selecting this modality for diagnosing indeterminate biliary strictures.
6. Current ERCP‐based tissue sampling methods have suboptimal sensitivity for the diagnosis of cholangiocarcinoma in primary sclerosing cholangitis (EL‐IB, RG‐A, VOR‐A, 85%; B, 15%; C, 0%; D, 0%).
…”
Section: Resultsmentioning
confidence: 99%
“…The inter‐observer agreement in interpretation of probe‐based confocal laser endomicroscopy imaging for indeterminate biliary strictures was reported poor or fair in a prospective, multicentre pilot study . Another prospective, multicentre study showed that the diagnostic accuracy for indeterminate biliary strictures could be improved significantly after training with expert user of probe‐based confocal laser endomicroscopy, which highlights the necessity and importance of training before selecting this modality for diagnosing indeterminate biliary strictures.
6. Current ERCP‐based tissue sampling methods have suboptimal sensitivity for the diagnosis of cholangiocarcinoma in primary sclerosing cholangitis (EL‐IB, RG‐A, VOR‐A, 85%; B, 15%; C, 0%; D, 0%).
…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the reproducibility of pCLE interpretation in real time and off line by blinded observers. 19 In this study, we recognized the association between clinical impression and the interpretation of pCLE and chose to record the real-time impression of the endoscopist performing the ERCP, because this represents the factor that will drive clinical decision making. This is a unique metric used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Talreja et al demonstrated substantial agreement with improved diagnostic accuracy in a followup study that incorporated a standardized classification system and a single teaching session. 21 Liu et al demonstrated a similar quick learning curve when agreement (j) was significantly higher in the experienced group over the inexperienced group in only the first set of four image sets. 16 Although we did not directly test for learning curve, we believe that we achieved substantial agreement due to pretest training using predefined image classification criteria.…”
Section: Discussionmentioning
confidence: 83%
“…In comparison, studies by Bakhru et al and Talreja et al demonstrating only poor to fair agreement in GI applications both cited a need for a standardized system of pCLE image classification, as well as a need for formal training . Talreja et al demonstrated substantial agreement with improved diagnostic accuracy in a follow‐up study that incorporated a standardized classification system and a single teaching session . Liu et al demonstrated a similar quick learning curve when agreement (κ) was significantly higher in the experienced group over the inexperienced group in only the first set of four image sets .…”
Section: Discussionmentioning
confidence: 97%